Muslim Perkotaan di Tengah Pusaran Pilkada 2017 di Kota Yogyakarta - Isnanto, Muh (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2018)
In the 2017 elections in the city of Yogyakarta, which used to be the basis for the number 1 candidate’s voice bag carrying Imam Priyono-Ahmad Fadli suffered defeat, this event if connected with the product 3 times the election in the reform era, this may not have much benefit to the lives of the people, the leaders or respected members of the council are still busy thinking about the bearer party rather than thinking about the interests and or needs of the real people, especially the welfare of the people in general. The problem is how high is the level of concern of urban Muslims in the city of Yogyakarta towards the candidate pair (Paslon) in the 2017 elections and why are urban Muslim communities like that, what are the factors? Research results show that, firstly, the level of concern of the urban Muslim community towards the Regional Head candidates in the 2017 elections. The community has started to use the basis of their rationality and religious awareness by always checking/recognizing their candidate pairs (47%), considering quality by never considering religious attributes 47%, always considering intelligence 53%, not considering gender 70% and ethnicity 69%, always considering 61% personality, 41% expertise, 45% participation. More than half (54%) warned that they knew that a candidate pair was using improper means and refused when a candidate in the election tripped over a case. More than half (52%) did not choose a candidate pair who tripped over the case. Report potential regional head pairs if someone cheats or violates the law. more than half (64%) report to the authorities. Secondly, factors that cause high concern because of the institutionalization of democracy, the election as a shortcut; and religious awareness